2008
DOI: 10.1063/1.2953972
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-protected iron layer on Ni(111)

Abstract: Here we report the photoemission studies of intercalation process of Fe underneath graphene layer on Ni(111). The process of intercalation was monitored via XPS of corresponding core levels and UPS of the graphene-derived π states in the valence band. fcc-Fe films with thickness of 2-5 monolayers at the interface between graphene and Ni(111) form epitaxial magnetic layer passivated from the reactive environment, like for example oxygen gas.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
141
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 15 publications
(25 reference statements)
11
141
0
7
Order By: Relevance
“…2(a): a much larger separation between π and π * at the K point is observed. We attribute this to the intercalation of potassium atoms into the graphene/Au interface, consistent with the behavior of other metals (Au, Ag, Fe, Cu...) that readily intercalate in between the interface of graphene and the Ni substrate 7,19,27,28 . The intercalation at RT is also consistent with the reported 100 K temperature limit above which potassium ions on a graphene sheet become mobile 29 .…”
Section: Resultsmentioning
confidence: 56%
“…2(a): a much larger separation between π and π * at the K point is observed. We attribute this to the intercalation of potassium atoms into the graphene/Au interface, consistent with the behavior of other metals (Au, Ag, Fe, Cu...) that readily intercalate in between the interface of graphene and the Ni substrate 7,19,27,28 . The intercalation at RT is also consistent with the reported 100 K temperature limit above which potassium ions on a graphene sheet become mobile 29 .…”
Section: Resultsmentioning
confidence: 56%
“…Above that, a single atom thick graphene layer can effectively protect the underlying material against oxidation and/or corrosion [11,12]. This property is particularly exciting when graphene is deposited or formed on the surface of a ferromagnet or a material which exhibits strong spin-orbit interaction [13][14][15][16][17][18][19]. Here, interfacial contact between graphene and the respective material might lead to the appearance of different new phenomena in graphene and at the interface, such as induced magnetism in graphene [20][21][22], possible induced spin-orbit splitting of the graphene π states [23,24], conservation of spin-polarized electron emission from the underlying ferromagnetic material [13,15], etc.…”
mentioning
confidence: 99%
“…Being an ultra-thin, strong and light material, graphene 7 has been viewed as an ideal nanocoating material. Various metal surfaces including Ni, 8,9 Ru(0001), 10 Cu/Ni alloy, 11 Cu, 12,13 Ir(111), and Pt(111) 14 have been coated by graphene and a reduction in the oxidation of the surface was reported. It was theoretically shown that even graphene itself strongly interacts with oxygen atoms, it poses a high energy barrier for the penetration of oxygen and thus can protect the surface underneath against oxidation as long as the graphene coating is defect free.…”
Section: Introductionmentioning
confidence: 99%